2013
DOI: 10.5535/arm.2013.37.5.675
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Mobility, Vertebral Squaring, Pulmonary Function, Pain, Fatigue, and Quality of Life in Patients With Ankylosing Spondylitis

Abstract: ObjectiveTo investigate the relationships between spinal mobility, pulmonary function, structural change of the spine, pain, fatigue, and quality of life (QOL) in patients with ankylosing spondylitis (AS).MethodsThirty-six patients with AS were recruited. Their spinal mobility was examined through seven physical tests: modified Schober test, lateral bending, chest expansion, occiput to wall, finger to ground, bimalleolar distance, and range of motion (ROM) of the spine. Pulmonary Function Test (PFT) was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 32 publications
1
33
0
Order By: Relevance
“…However, surgery for spinal fractures associated with AS is complex and replete with risk due to multiple factors [4,5]. Patients with AS often have greater comorbidities, such as hyperkyphosis-related reduction in pulmonary function [12][13][14]. Increased risk of spinal cord injury due to instability of the fracture necessitates careful consideration of transfers and operative positioning [3,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…However, surgery for spinal fractures associated with AS is complex and replete with risk due to multiple factors [4,5]. Patients with AS often have greater comorbidities, such as hyperkyphosis-related reduction in pulmonary function [12][13][14]. Increased risk of spinal cord injury due to instability of the fracture necessitates careful consideration of transfers and operative positioning [3,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…A study that examined disease activity, quality of life, fatigue, pain and physical condition reported that low physical condition and high levels of pain result in reduced quality of life; high disease activity, reduced functionality and increased fatigue. 34 It can be mentioned that patients with high disease activity feel more pain and fatigue and therefore show less functionality leading to reduced exercise capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral arthritis and enthesopathy have been reported to be present in a large group of AS patients (1). In addition, specific organ involvement including anterior uveitis, psoriasis and chronic inflammatory bowel disease, may simultaneously occur in AS, accompanied by an increased risk of cardiovascular or pulmonary complications (1,2). Chronic inflammation in the attachment of tendons, ligaments and joint capsules to bone leads to alterations in joint architecture, with new bone formations and joint fusions (3).…”
Section: Introductionmentioning
confidence: 99%